2021
DOI: 10.3390/molecules26206197
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Based Natural Products and Extracts: Potential Source to Develop New Antiviral Drug Candidates

Abstract: Viral infections are among the most complex medical problems and have been a major threat to the economy and global health. Several epidemics and pandemics have occurred due to viruses, which has led to a significant increase in mortality and morbidity rates. Natural products have always been an inspiration and source for new drug development because of their various uses. Among all-natural sources, plant sources are the most dominant for the discovery of new therapeutic agents due to their chemical and struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 162 publications
(73 reference statements)
0
33
0
Order By: Relevance
“…Herbal bioactive compounds due to their high chemical-diversity and biochemical-specificity have been extensively studied for their therapeutic potential against different diseases. Of these, various herbal formulations and isolated compounds belonging to different classes such as flavonoids, alkaloids, tannins, saponins, lignans, coumarins, polyphenols, glycosides, and terpenoids have been widely reported for their antiviral efficacies against several pathogenic viruses [15][16][17].…”
Section: Viral Diseases and Herbal Antiviralsmentioning
confidence: 99%
“…Herbal bioactive compounds due to their high chemical-diversity and biochemical-specificity have been extensively studied for their therapeutic potential against different diseases. Of these, various herbal formulations and isolated compounds belonging to different classes such as flavonoids, alkaloids, tannins, saponins, lignans, coumarins, polyphenols, glycosides, and terpenoids have been widely reported for their antiviral efficacies against several pathogenic viruses [15][16][17].…”
Section: Viral Diseases and Herbal Antiviralsmentioning
confidence: 99%
“…As recently reported, viruses are responsible for several human diseases and novel phytochemicals interact with the viral life cycle, viral entry, replication, assembly, and release [10][11][12][13]. Therefore, natural products are promising candidates for broad application.…”
Section: Introductionmentioning
confidence: 97%
“…Currently, plant-derived antiviral agents are widely used because natural products are cheap and available in the local areas. Some plants have low toxicity and can prevent microbial infections [ 9 ]. Recently, more evidence has shown that plant-based products could be an alternative therapeutic agent for combating some viral infection by accelerating the disease recovery period or protecting animals during the time lag between vaccination and immunity [ 10 ].…”
Section: Introductionmentioning
confidence: 99%